Utilization of NGS technologies to investigate transcriptomic and epigenomic mechanisms in trastuzumab resistance - Nava, Miguel (Sci Rep, 2019)
NGS (Next Generation Sequencing) technologies allows us to determine key gene expression signatures that correlate with resistance (and responsiveness) to anti-cancer therapeutics. We have undertaken a transcriptomic and chromatin immunoprecipitation followed by sequencing (ChIP-seq) approach to describe differences in gene expression and the underlying chromatin landscape between two representative HER2+ cell lines, one of which is sensitive (SKBR3) and the other which is resistant (JIMT1) to trastuzumab. We identified differentially expressed genes (DEGs) and differentially expressed transcripts (DETs) between SKBR3 and JIMT1 cells. Several of the DEGs are components of the Polycomb Repressing Complex 2 (PRC2), and they are expressed higher in JIMT1 cells. In addition, we utilized ChIP-seq to identify H3K18ac, H3K27ac and H3K27me3 histone modifications genome-wide. We identified key differences of H3K18ac and H3K27ac enrichment in regulatory regions, found a correlation between these modifications and differential gene expression and identified a transcription factor binding motif for LRF near these modifications in both cell lines. Lastly, we found a small subset of genes that contain repressive H3K27me3 marks near the gene body in SKBR3 cells but are absent in JIMT1. Taken together, our data suggests that differential gene expression and trastuzumab responsiveness in JIMT1 and SKBR3 is determined by epigenetic mechanisms.